Effect of Tb4O7 content on the optical and mechanical properties of transparent ceramics based on MgAl2O4; Materials Today: Proceedings; Vol. 19, Pt. 5 : International Conference on Modern Trends in Manufacturing Technologies and Equipment 2019 - Paygin V. D. Vladimir Denisovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich (2019, 2019)
Title screen